Electrodepositon of Dendritic Ni-Co onto High-Voltage Electrodes of Electrostatic Particulate Matter (PM) Sensors. Issue 6 (1st January 2016) - Copenhaver, Katherine; Allmendinger, Klaus; Beckert, Michael; Boettcher, Michael; Fitzpatrick, Joseph; Henderson, Brett; Nadler, Jason; Woo, Leta
Abstract : Particulate matter (PM) or soot sensing technologies are needed for feedback and control of exhaust after-treatment systems to meet increasingly stringent environmental regulations. A novel low-cost electrostatic PM sensing approach has recently been developed based on a concentric electrode design with a central cylindrical high-voltage electrode surrounded by an inner baffle that serves as the ground/negative terminal. The sensing principle is not completely understood, but seems to rely on capturing naturally combustion charged particles on electrode surfaces where a delay in sensor startup time occurs during initial testing. We examined the influence of dendritic Ni-Co coatings on PM sensor performance and demonstrated an improvement in startup time for an optimized coating morphology when compared with bare non-coated control electrodes. The influence of the dendritic Ni-Co coating could be related to altering the interaction of PM with specific morphological surface features of the dendritic Ni-Co coating on the high-voltage electrode.